Exploring EFL Students’ Speaking Anxiety in Microsoft Teams Classroom Discussion Learning - Rahmania, Melita Alit; Pahlevi, Muhammad Reza; Sumarta, Sumarta (English Education: Jurnal Tadris Bahasa Inggris, 2022)
This case study reported on how students experienced speaking anxiety in online EFL classrooms. The data was obtained through observation, questionnaires on a google form, and interviews. The data analysis technique used was thematic analysis. The participants consisted of second-year students from one vocational school in Indonesia determined as many as 14 (fourteen) students, 4 representative students were chosen using FLCAS for the Interview, and 14 students for the FLCAS Questionnaire. The questionnaire sheet obtained feedback on students' types of speaking anxiety are (a) test anxiety, (b) fear of negative judgment, and (c) communicative apprehension. Data analysis showed that speaking anxiety can be influenced by several factors including fear speak in front of peers, fear of negative feedback, and fear of failure. In addition, the analysis discovered that (1) preparation, (2) relaxation, (3) positive thinking, (4) peer thinking, (5) positive outlook, and (6) using useful tools were strategies used by students to overcome speaking anxiety.